Activation of Tissue Reparative Processes by Glow-Type Plasma Discharges as an Integral Part of the Therapy of Decubital Ulcers - Sergej V. Belov; Yurij K. Danilejko; Sergey V. Gudkov; Aleksej B. Egorov; Vladimir I. Lukanin; Vladimir B. Tsvetkov; Evgeny L. Altukhov; Marina V. Petrova; Alexey A. Yakovlev; Elkhan G. Osmanov; Mikhail V. Dubinin; Evgenia A. Kogan; et al. (Applied Sciences, 2022)
The results of a clinical study of the complex treatment of pressure ulcers using the method of activation of reparative processes in tissues by cold plasma discharges initiated by high-frequency current are presented. Activation was carried out with a specialized device generating cold plasma discharges at frequencies of 0.11, 2.64, and 6.78 MHz. It was shown that the process of activation in the skin and muscle tissues of the bedsore zone proceeds most efficiently when using a current with a frequency of 6.78 MHz as compared to currents with a frequency of 2.64 and 0.11 MHz. For a needle electrode with a diameter of 0.3 mm, the optimal exposure parameters were power—(5.0 ± 1.5) W and time—(2.0–3.0) s. The results of the analysis of histological samples, histochemical, and bacteriological analysis confirmed the effect and showed the dynamics of the process of activation of reparative processes in the tissues of the bedsore wound under the influence of cold plasma discharges and a decrease in microbial contamination. The most pronounced effect of activation was formed during the period from 14 to 21 days. The effectiveness of therapy by the method of activation of reparative processes with cold plasma discharges, according to the criterion of the rate of wound healing, ranged from 14 to 16%, depending on the etiology of the decubitus wound. It is concluded that the activation of tissue reparative processes by glow-type plasma discharges as an integral part of the treatment of decubital ulcers is an effective link in the complex treatment of pressure sores.